ANALYSIS OF MUSLIM CONSUMER PREFERENCES IN BUYING SKINCARE PRODUCTS - Ma'ruf, Aminudin; Alam, Azhar; Syaraf, Ahsan Barra (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study investigates the determinants of a Muslim consumer in buying skincare products considering the attributes exist in skincare products. The purpose of this study is to find out the components of skincare products shaping the preferences of Muslim costumers in buying skincare products. Moreover, this study specifically attempts to identify the most significant aspect influencing the preferences of Muslim consumers. This study is a field research study with the sample of study of University Students in Surakarta. The result complies the previous studies on the topic and gives a pivotal input for skincare industry. This study recommended a robust framework for halal products to compete with its counterparts and suggested the policy makers on designing an environmental friendly products leading the nation’s economy and long-term prosperity.